Reaction kinetic behaviour with relation to crystallite/grain size dependency in the Mg-Si-H system - Chaudhary, A.; Sheppard, Drew; Paskevicius, M.; Pistidda, C.; Dornheim, M.; Buckley, Craig (Elsevier Ltd, 2015)
© 2015 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved. An empirical understanding of the relationship between crystallite size and reaction kinetics for the dehydrogenation of MgH2 in the presence of Si was determined. MgH2 was combined with Si under different conditions to obtain varying crystallite sizes of both reactants. Thermal analysis and isothermal desorption were undertaken to obtain reaction kinetic information and therefore determine activation energies as well as the rate limiting step for each of the different crystallite sizes. It was found that there is a strong correlation between crystallite size and activation energy for the growth of the Mg2Si phase, however, any correlation between the nucleation (of Mg2Si) activation energy was less evident. Direct measurements of kinetic behaviour from a manometric Sieverts apparatus showed that initial reaction kinetics were fastest when MgH2 was mixed with Si nanoparticles, however, this sample was not able to fully desorb. Data from the Sieverts measurements were then used with well-known theoretical models to determine the rate limiting step of the reaction. The three dimensional Carter-Valensi (or contracting volume) diffusion model could be used to describe the rate limiting step for most of the reactions. These results have led to a proposed mechanism for the formation of Mg2Si during the decomposition reaction.